The physics of rubber elasticity - Treloar, L. R. G. (Clarendon Press ; Oxford University Press, 2005)
This book provides a critical review of the equilibrium elastic properties of rubber, together with the kinetic-theory background. It is suitable for the non-specialist and the emphasis is on the physical reality embodied in the mathematical formulations. - ;This book provides a critical review of the equilibrium elastic properties of rubber, together with the kinetic-theory background. It is suitable for the non-specialist and the emphasis is on the physical reality embodied in the mathematical formulations. Polymer science had developed greatly since the second edition of this text in 1958.
Keywords: Rubber -- Elastic properties.; elektronické knihy; electronic books